2019
DOI: 10.3390/microorganisms7090337
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Screening and Expression Analysis of Psychrophilic Bacillus spp. Reveal Their Potential to Alleviate Cold Stress and Modulate Phytohormones in Wheat

Abstract: Abiotic stress in plants pose a major threat to cereal crop production worldwide and cold stress is also notorious for causing a decrease in plant growth and yield in wheat. The present study was designed to alleviate cold stress on plants by inoculating psychrophilic PGPR bacteria belonging to Bacillus genera isolated from extreme rhizospheric environments of Qinghai-Tibetan plateau. The genetic screening of psychrophilic Bacillus spp. CJCL2, RJGP41 and temperate B. velezensis FZB42 revealed presence of genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 80 publications
3
56
0
Order By: Relevance
“…The rice plants treated with PXO99 A and sterilized with double distilled water were used as controls. The time frame study for consumption of CO 2 as well as light usage depicting photosynthetic activity, transpiration rate and stomatal conductance of rice plants was performed by using the readings from seven maximum light exposed leaves from three plants of each treatment post inoculation (at an interval of 2, 4 and 6 dpi) by using an open IRGA LI-COR 6400 XT portable photosynthesis system (LI-6400, Li-Cor Inc., Lincoln, NE, USA) [34]. All parameters under study were recorded under light saturated conditions at 380 mol mol −1 CO 2 concentration and a photosynthetic photon flux density of 1000 mmol photons m −2 s −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The rice plants treated with PXO99 A and sterilized with double distilled water were used as controls. The time frame study for consumption of CO 2 as well as light usage depicting photosynthetic activity, transpiration rate and stomatal conductance of rice plants was performed by using the readings from seven maximum light exposed leaves from three plants of each treatment post inoculation (at an interval of 2, 4 and 6 dpi) by using an open IRGA LI-COR 6400 XT portable photosynthesis system (LI-6400, Li-Cor Inc., Lincoln, NE, USA) [34]. All parameters under study were recorded under light saturated conditions at 380 mol mol −1 CO 2 concentration and a photosynthetic photon flux density of 1000 mmol photons m −2 s −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Bacteria of the genus Arthrobacter , Bacillus , Janthinobacterium , Pseudomonas , and Sporosarcine , among others, have been described as having different mechanisms associated with cold stress tolerance, such as cold acclimation proteins (Caps) and antifreezing proteins (AFPs) that protect the specific cytoplasmic and extracellular components involved in cold adaptation [ 55 ]. In addition, a study by Zubair et al [ 67 ] showed that the Bacillus genus presents mechanisms of response to cold stress through the formation of biofilms, the production of Reactive Oxygen Species (ROS), and also through the expression of the acdS gene, which is related to the ACC deaminase activity committed to the PGP capacity.…”
Section: Resultsmentioning
confidence: 99%
“…NARs9 compared to 71% control germination, after 7 days at 18 • C. Yarzábal et al [26] showed an increase of around 32% in the length of roots of wheat seeds treated with the Antarctic Pseudomonas sp. CIBEA71 compared to the control treatment, after 5 days at 16 • C. Zubair et al [27] reported that the treatment with Bacillus strains increases the vigor index of wheat seeds after 7 days at 14 • C.…”
Section: Discussionmentioning
confidence: 99%
“…CIBEA71 compared to the control treatment, after 5 days at 16 °C. Zubair et al [ 27 ] reported that the treatment with Bacillus strains increases the vigor index of wheat seeds after 7 days at 14 °C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation